Growth Mindset dan Stres Akademik Pada Siswa SMA di Yogyakarta - Henny Alina Khilma; Narastri Insan Utami (FAKULTAS TARBIYAH INSTITUT AGAMA ISLAM SULTAN MUHAMMAD SYAFIUDDIN SAMBAS, 2024)
The purpose of this study was to determine the relationship between growth mindset and academic stress in high school students in Yogyakarta. The hypothesis in this study is that there is a significant relationship between growth mindset and academic stress in high school students in Yogyakarta. The higher the growth mindset, the lower the academic stress in high school students in Yogyakarta. Conversely, the lower the growth mindset, the higher the academic stress in high school students in Yogyakarta. The hypothesis in this study is accepted. The subjects in this study involved 110 high school students in Yogyakarta.. The data collection method in this study is a scale and there is a psychological scale used in this study, namely the growth mindset scale with academic stress. The study results obtained a correlation coefficient (rxy) = 0.946 and p = 0.001 (p ≤ 0.01). Which means there is a positive relationship between growth mindset and academic stress in high school students in Yogyakarta. The higher the growth mindset, the lower the academic stress in high school students in Yogyakarta. Conversely, the lower the growth mindset, the higher the academic stress in high school students in Yogyakarta. The hypothesis in this study is accepted. The coefficient of determination or coefficient of determination (R2) obtained was 0.894, which means the contribution of growth mindset and academic stress was 89.4%. This shows that as much as 10.6% is caused by other variables.